Long-term follow-up of patients treated with aminosalicylates for ulcerative colitis: Predictive factors of response: An observational case-control study. Issue 8 (October 2019) - Marti-Aguado, David; Ballester, María Pilar; Tosca, Joan; Bosca-Watts, Marta Maia; Navarro, Pablo; Anton, Rosario; Pascual, Isabel; Mora, Francisco; Minguez, Miguel
Background: Knowing patients' ulcerative colitis history is essential to selecting the appropriate therapy according to risk stratification. Objective: To evaluate and identify predictive factors of non-response to aminosalicylates judged as the need for a step-up approach over time. Methods: A case-control study of ulcerative colitis patients treated with aminosalicylates after the diagnosis of disease flare included in the ENEIDA single-centre registry from 1997 to 2017. Long-term treatment maintenance with aminosalicylates and higher therapeutic requirements were recorded. The cumulative incidence of treatment escalation was estimated using Kaplan-Meier curves and compared by the log-rank test. Cox regression analysis was performed to identify predictive factors of treatment with immunomodulators, biological agents or surgery. Results: A total of 457 patients were included, of whom 28% ( n  = 126) were non-responders to aminosalicylates. The cumulative probability for a step-up approach within 20 years of follow up was 35%, mainly due to steroid-dependent colitis. Risk factors for treatment escalation were age ≤27 years (hazard ratio 2.31, 95% confidence interval 1.36–3.92), extensive colitis (hazard ratio 1.65, 95% confidence interval 1.04–2.60), Mayo endoscopic subscore ≥2 (hazard ratio 1.45, 95% confidence interval 1.02–2.06) and extraintestinal manifestations (hazard ratio 2.04, 95% confidence interval 1.03–4.05). Conclusions: Aminosalicylates represent an effective maintenance therapy. Younger age, extensive colitis, endoscopic disease severity and extraintestinal manifestations are risk factors for higher therapeutic requirements.